Suling Saih Roras : A Development of Balinese Flute Instrumentation| Suling Saih Roras : Sebuah Pengembangan Dari Instrumentasi Suling Bali - Werdi Saputra; I Nyoman Mariyana (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Suling Saih Roras is an experimental music work that uses Suling Saih Roras instrument as the reveal media. A wind instrument that inspires this musical work in Bali is the flute. Based on that, the composer observed the tones generated by the six holes could be developed, resulting in an initiative to establish the tones in the flute. Creating that meant in this working process is, the composer developed a flute that previously had six holes developed become 11 holes so can show the tones that previously unexplored in 6 holes flute. The stages included in this theory are Purpose, Talent, Creativity, Local Culture, Working Concept, Praying, Work Implementation, Work Tryout, and Establishing Concept and Form. The structure of this musical work is divided into four parts: the first part introduces the tones area on Suling Saih Roras. The composer introduced the tones contained in Suling Saih Roras Instrument. In the second part, highlight each instrument. Start with the most prominent flute, big, medium, and small flute. This aimed to highlight the sound characteristics of each side of the flute. The third part of this work is their harmony and modulation processing. The fourth part integrates the points contained in the three previous sections. In this section, the composer also explores the timbre of Suling Saih Roras Instrument.